Associated factors to the occurrence of motorcycle accident in the perception of hospitalized motorcyclist - doi:10.5020/18061230.2010.p213 - Augediva Maria Jucá Pordeus; Luiza Jane Eyre de Souza Vieira; Paulo César de Almeida; Luciene Miranda de Andrade; Ana Carine Goerschi Silva; Samira Valentim Gama Lira (Revista Brasileira em Promoção da Saúde, 2012)
Objective: To describe the social demographic characteristics of injured motorcyclists admitted into an emergency hospital and their perception about the accident. Methods: A cross-sectional study conducted between October and December 2007 with a sample of 209 patients who were victims of motorcycle accidents. A form was applied for data collection and the data were submitted to frequency analysis. The studied variables comprised social demographic data; conditions of the accident; the use of alcohol and the perception of the victim in relation to the accident. Results: Out of 209 interviewed patients, 183 (88%) were male, 88 (42%) were aged 21 to 30 years; 147 (65.9%) were from different counties of the accident site, 89 (53.9%) were not licensed riders; 93 (56.3%) did not wear a helmet and 113 (54.4%) reported drinking alcohol before the accident. Regarding the perception of the victims about the cause of the accident, 90 (43%) highlighted the inappropriate behavior of their own rider. Conclusion: The study revealed that among injured motorcyclists, prevailed males, young and single, who did not wear helmet at the time of the accident, who were not legally qualified to drive a motorcycle and who recognize as the main cause of these accidents their own inadequate behavior